Replication of acetylaminofluorene-adducted plasmids in human cells: spectrum of base substitutions and evidence of excision repair. - Mah, M C (1991)
In rats fed the liver carcinogen 2-acetylaminofluorene (AAF), the two most abundant types of DNA adduct are N-(deoxyguanosin-8-yl)-2-acetylaminofluorene and its deacetylated derivative. When plasmids carrying AAF adducts replicate in bacteria, the predominant mutations are frameshifts, whereas with deacetylated (AF) adducts, they are mainly base substitutions, just as we found when plasmids carrying AF adducts replicated in human cells. We have investigated the frequency and spectrum of mutations induced when a shuttle vector carrying AAF adducts (85% bound to the C8 position of guanine, 15% to the N2 position) replicated in human cells. The frequency induced per initial AAF adduct was higher than with AF adducts, but the kinds of mutations were similar--i.e., 85% base substitutions, principally G.C----T.A transversions. There was good correlation between the "hot spots" for mutations and hot spots for AAF adduct formation, suggesting that mutational hot spots reflect preferential binding of the carcinogen to DNA. 32P-postlabeling analysis of the adducts before and after the DNA was transfected into the human cells showed that there was no deacetylation of AAF adducts and that 85% of both types of adducts were removed within 3.5 hr, most probably by excision repair.